The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/suco.201700234
|View full text |Cite
|
Sign up to set email alerts
|

Properties of self‐compacting concrete containing copper slag aggregate after heating up to 400°C

Abstract: In this paper, the influence of heating up to 400°C on properties of the self‐compacting concrete containing recycled copper slag fine aggregate was investigated. The residual mechanical properties such as compressive strength, splitting tensile strength, elastic modulus, and stress–strain curve of the heated concrete were measured with the change in the porosity of concrete. Moreover, the resistance against the penetration of chloride ions (Cl−) into the concrete after the heating was also evaluated. For obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The strength of concrete with less than 40% of CS replacement for fine aggregate was higher than or equal to that of the control specimen and also RCC concrete elements have a considerable of amount of strength increased in the compressive, split tensile, flexural characteristics, and energy absorption characteristics . Wei Gong et al investigated the influence of heating up to 400°C on properties of the self compacting concrete containing recycled CS fine aggregate and reported that reduction of compressive strength is not severe when the replacement rate is less than 40% CS . Whereas the load at first crack of the beam is increased by 8.1% for FA20CS80 and ultimate load carrying capacity also higher than the control concrete beams.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of concrete with less than 40% of CS replacement for fine aggregate was higher than or equal to that of the control specimen and also RCC concrete elements have a considerable of amount of strength increased in the compressive, split tensile, flexural characteristics, and energy absorption characteristics . Wei Gong et al investigated the influence of heating up to 400°C on properties of the self compacting concrete containing recycled CS fine aggregate and reported that reduction of compressive strength is not severe when the replacement rate is less than 40% CS . Whereas the load at first crack of the beam is increased by 8.1% for FA20CS80 and ultimate load carrying capacity also higher than the control concrete beams.…”
Section: Resultsmentioning
confidence: 99%
“…24 Wei Gong et al investigated the influence of heating up to 400 C on properties of the self compacting concrete containing recycled CS fine aggregate and reported that reduction of compressive strength is not severe when the replacement rate is less than 40% CS. 25 Whereas the load at first crack of the beam is increased by 8.1% for FA20CS80 and ultimate load carrying capacity also higher than the control concrete beams.…”
Section: Cracking Loads and Ultimate Loads On Beamsmentioning
confidence: 88%
“…Behavior of NWSCC is represented in Figure 31 [ 75 , 101 , 102 , 103 , 104 , 105 ]; the wide variety of the results is a consequence of the difference in the constituents used in the making of the SCC samples. NWSCC seems to show an increase in residual compressive strength mostly between 200 °C and 400 °C.…”
Section: Response Of Different Concrete Types Exposed To Elevated Tem...mentioning
confidence: 99%
“…For the damage identification of reinforced concrete (RC) structures at room temperature, researchers have conducted various theoretical analysis and experimental studies 3,4 . However, the identification of structural damages and material properties under high temperatures is relatively limited 5–7 . Seyed and Mohammad 5 used the natural frequency as input data to a support vector machine (SVM) and beam‐column connection damage characteristics as the SVM output data to detect frame node damages.…”
Section: Introductionmentioning
confidence: 99%